Review of Restaurant Tax Compliance Control Through Electronic Cash Register (ECR) Based on Fiscal Machinery - Heffy Harfiasarie; Musmuliadi Musmuliadi; Agustinus Djiu (Journal Research of Social Science, Economics, and Management, 2022)
The implementation of the fiscal machine-based Electronic Cash Register (ECR) installation program carried out by the West Kutai Regency Government is interesting and important to examine to find out and review how it is implemented, what are the obstacles faced in the implementation of the fiscal machine-based ECR machine and the district government's efforts. West Kutai is facing the problem of installing an ECR engine based on the fiscal engine. This study identifies the implementation of ECR to be researched, the results of which are recommendations to the government of West Kutai Regency in terms of overcoming or controlling it so that this research is very useful for the academic community as a community in developing knowledge in supporting development. This study aims to review the implementation of restaurant tax compliance control through ECR,public interest (consumers) to eat at restaurants using the Electronic Cash Register (ECR) is increasing or decreasing and its effect on restaurant tax revenue receipts,obstacles encountered in the implementation and subsequent efforts with regard to ECR. In this study using a qualitative type of research, this research by using a qualitative approach triangulates to get suggestions or recommendations from research results, namely for the development of research loci in the Regional Revenue Agency (Bapenda) of West Kutai Regency as a practical significance and final conclusion which can be in the form of conceptualization or formation policy theory obtained from research as academic significance. To facilitate the research, data collection techniques were used, including: interviews, observation and documentation. After the data is collected, the data reduction process is carried out, the data presentation and the last process is drawing conclusions.